Understanding arsenic toxicity: Implications for environmental exposure and human health - Ravidarshdeep kaur; Atul Garkal; Lopmudra Sarode; Priyanka Bangar; Tejal Mehta; Dhirendra Pratap Singh; Rakesh Rawal (Journal of Hazardous Materials Letters, 2024)
Arsenic is a trace element and a metalloid which is prominently known as an environmental hazard. At present, rising health apprehensions are linked to emanating from a wide array of industrial, chemical, residential, agricultural, and technological sources, leading to extensive pollution of water, soil, and air ecosystems including flora, fauna and humans. It poses significant harm to biological organisms upon acute and chronic exposure. In this review, we delve into the reported experimental data that elaborates on arsenic as a toxicant, with particular emphasis on its occurrence, metabolism and diverse molecular mechanisms involved. It also includes the major molecular mechanisms leading to systemic toxicity with special emphasis on shedding light on the intricate ways it disrupts the nervous system.